Revisiting particle kinetics in the rumen: comminution, digestion and passage functions as affected by diet type - De Vega A.; Gasa J.; Castrillo C.; Guada J.A. (Innovation for sustainability in sheep and goats, 2019)
Six Rasa Aragonesa wethers were fed lucerne hay either chopped at 5 cm (diet C) or ground (2 mm) and pelleted (diet P) in a cross-over design. Access to the diets was restricted to 4 hours, and fractional outflow rates from the rumen of liquid- (Co-EDTA) and solid-phase (Cr and Yb) markers, and digestion kinetics of different particle sizes (0.5-1 mm, 1-2 mm, 2-4 mm and 4-8 mm) were studied. Samples of rumen content were obtained at different times throughout the day to estimate rumen pools of different particle sizes, and dilution rates of transit markers and rumen volume. Feeding behaviour of the animals was also recorded. Dry matter intake was lower (P<0.001) in animals fed diet C than P (1206 vs. 1733 g/day) which on the other hand spent more time eating (218 vs. 94 min/day, or 182 vs. 55 min/kg dry matter intake-DMI; P<0.001) and ruminating (283 vs. 182 min/kg DMI; P<0.05). Potential degradability of different particle sizes did not change across diet types whereas fractional degradation rate decreased (P < 0.01) as particle size increased. The mean particle size of rumen digesta was higher with diet C (P < 0.05) whereas the rate at which particles larger than 1.2 mm reduced due to chewing during eating was higher with diet P than C, but the effectiveness of rumination in reducing particle size of rumen digesta was higher with diet C. The higher intakes in animals fed diet P could be explained by variations in rumen volume, rates of digestion and a higher rate of outflow of small particles pulled out with the liquid phase.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)